VIETNAMESE PREHISTORIC MARINE CULTURES - OUTSTANDING HISTORICAL AND CULTURAL VALUES - Nguyễn Khắc Sử (Tạp chí Khoa học Đại học Đà Lạt)
Vietnamese prehistoric marine culture is the culture of ancient communities who had no written languages, social classes, or states. The inhabitants lived in coastal environments, exploited marine resources, had relations with broad surrounding areas, and created a bold marine culture (Nguyen, 1997, pp. 16-28). Earth's history has gone through at least 20 glacial and interglacial cycles in which the sea advanced and receded, not to mention the small fluctuations between stages, or those due to tectonic activity that made sea-level changes vary in each region. Fluctuations in past water levels in the East Sea determined not only the space for survival, but also the process of forming prehistoric Vietnamese marine cultures. This article discusses the following issues: The history of exploiting seas and islands, the process of developing ancient Vietnamese oceanic cultures, cultural-historical values, and the position of maritime culture in the broader context.